2018
DOI: 10.4310/atmp.2018.v22.n1.a2
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of geodesic completeness in the Brinkmann class of gravitational wave spacetimes

Abstract: We consider restrictions placed by geodesic completeness on spacetimes possessing a null parallel vector field, the so-called Brinkmann spacetimes. This class of spacetimes includes important idealized gravitational wave models in General Relativity, namely the plane-fronted waves with parallel rays, or pp-waves, which in turn have been intensely and fruitfully studied in the mathematical and physical literatures for over half a century. More concretely, we prove a restricted version of a conjectural analogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Indeed, the progress along these decades has focused on other aspects of the conjecture rather than in the crude geodesic equation (or the dynamical system (4)), concretely: (a) All plane waves (gravitational or not) are geodesically complete, as the equation (4) reduces to a second order linear system of differential equations [17], [ [26] gave a local characterization of pp-waves, argued that a natural extension of the conjecture follows when a locally pp-wave metric is taken on a compact M , and proved that this extension becomes equivalent to the standard one on R 4 . In this same line, the quoted article [16] also showed that plane waves are the universal coverings of certain spacetimes with non-trivial topology under some natural hypotheses for EK conjecture.…”
Section: 2mentioning
confidence: 86%
See 4 more Smart Citations
“…Indeed, the progress along these decades has focused on other aspects of the conjecture rather than in the crude geodesic equation (or the dynamical system (4)), concretely: (a) All plane waves (gravitational or not) are geodesically complete, as the equation (4) reduces to a second order linear system of differential equations [17], [ [26] gave a local characterization of pp-waves, argued that a natural extension of the conjecture follows when a locally pp-wave metric is taken on a compact M , and proved that this extension becomes equivalent to the standard one on R 4 . In this same line, the quoted article [16] also showed that plane waves are the universal coverings of certain spacetimes with non-trivial topology under some natural hypotheses for EK conjecture.…”
Section: 2mentioning
confidence: 86%
“…However, Leistner and Schliebner [26] gave a local characterization of pp-waves, argued that a natural extension of the conjecture follows when a locally pp-wave metric is taken on a compact M , and proved that this extension becomes equivalent to the standard one on R 4 . In this same line, the quoted article [16] also showed that plane waves are the universal coverings of certain spacetimes with non-trivial topology under some natural hypotheses for EK conjecture.…”
mentioning
confidence: 86%
See 3 more Smart Citations